2019
DOI: 10.1680/jgeot.18.p.004
|View full text |Cite
|
Sign up to set email alerts
|

The parkable piezoprobe for determining cv and strength – modelling and interpretation methods

Abstract: The parkable piezoprobe (PPP) is a site investigation tool for measuring the coefficient of consolidation, in-situ offshore, at shallow embedment depths. The device applies a similar bearing pressure to subsea infrastructure so reaches a comparable self-weight penetration when 'parked' at the seabed, representative of an unburied pipeline. Instrumentation on the device allows the dissipation of penetration-induced excess pore pressure to be recorded at various locations on the surface. From these dissipation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Figure 13 compares the inferred coefficients of consolidation with miniature piezocone (c h ) and Rowe cell (c v ) data measured independently in the same kaolin clay over the past decade or more at The University of Western Australia (Richardson 2007;Chow et al 2014;Cocjin et al 2014). Data at shallow embedment are conspicuously absent, but the shallow penetrometer data presented here are consistent with the measurements generated using the parkable piezoprobe, another device intended to measure surficial soil properties (Chatterjee et al 2014;Schneider et al 2019) and the back-extrapolated trends from the piezocone and Rowe cell data.…”
Section: Pore Pressure Dissipationsupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 13 compares the inferred coefficients of consolidation with miniature piezocone (c h ) and Rowe cell (c v ) data measured independently in the same kaolin clay over the past decade or more at The University of Western Australia (Richardson 2007;Chow et al 2014;Cocjin et al 2014). Data at shallow embedment are conspicuously absent, but the shallow penetrometer data presented here are consistent with the measurements generated using the parkable piezoprobe, another device intended to measure surficial soil properties (Chatterjee et al 2014;Schneider et al 2019) and the back-extrapolated trends from the piezocone and Rowe cell data.…”
Section: Pore Pressure Dissipationsupporting
confidence: 77%
“…A small surcharge, q 0 , of ϳ1 kPa (quasi-uniform conditions of s u and c v over depth range of interest, as q 0 /␥ D = 2) was required to achieve convergence at the free surface of the soil and to create a shear strength intercept at the mudline. The appropriateness of the adopted mesh density and penetration rate (V pen ϳ 100) was confirmed through sensitivity analyses (see also Schneider et al 2019).…”
Section: New Dissipation Solutions For Hemiball (Ldfe)mentioning
confidence: 93%
“…Mahmoodzadeh et al Schneider, M.A., Whittle, R.W. and Springman, S.M. Measuring strength and consolidation properties in lacustrine clay using piezocone and self-boring pressuremeter tests 21 isotropic pore water flow and permeability anisotropy seems to be one of the most prominent drivers of the observed discrepancy between field and laboratory measurements, the equation proposed by Mahmoodzadeh et al (2014) shall be extended by the findings from Schneider et al (2019) to give:…”
Section: Comparison and Discussion Of Test Resultsmentioning
confidence: 99%
“…7)whereas vʹ, α and f(n k ) represent the Poisson ratio, a weighting factor controlling the elastoplastic soil behaviour around the probe and a function incorporating the effects of anisotropic flow, respectively. Based on an extensive LDFE-study analysing the dissipation response of the Parkable Piezoprobe (shallow penetration of a hemispherical probe),Schneider et al (2019) found the following relationship: f(n k ) = (2n k +1)/3, which is essentially equivalent to the geometric mean of all three permeability components Wang et al (2015). found a similar expression for the piezoball.…”
mentioning
confidence: 99%
“…These were previously calibrated using standard geotechnical element tests performed on natural Pisa and reconstituted kaolin clay samples and the various parameters adopted are presented in Table 1. For the Pisa clay, the identification of the parameters [36], which has been adopted extensively in past numerical studies( [37], [38], [39], [40], [41]). Considering the effective stress levels important for the boundary value problem simulation presented later in this study (i.e.…”
Section: Materials Parameters and Model Validationmentioning
confidence: 99%